Pola Asuh Orang Tua Ideal Atas Anak - Adnan, Abu Bakar (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Godly children are the ultimate hope of parents for their children, but this achievement must go through a process, namely ideal parenting. The purpose of this research is to find the ideal parenting method to realize pious children. To achieve this goal, this research is qualitative, using a literature study approach by means of descriptive analysis. Islamic parenting is an ideal parenting pattern compared to other parenting patterns, namely authoritarian parenting, democratic parenting, and Laissez Prifer parenting. The specificity of Islamic Parenting is to include Allah SWT in every decision making of parents on children and emphasize the value of patience in carrying out the parenting process that other parenting patterns do not have.